Screening for Early Detection of Cervical Cancer in Women Living with HIV in Mumbai, India - Retrospective Cohort Study from a Tertiary Cancer Center - Pimple, Sharmila A.; Pahwa, Vandita; Mishra, Gauravi A.; Anand, Kavita V.; Pathuthara, Saleem; Biswas, Sanjay K. (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Women living with human immunodeficiency virus (HIV) have an increased risk of persistent human papillomavirus infection (HPV) of developing cervical cancer precursors and are, therefore, considered at higher risk for cervical cancer. Despite the higher risk, screening for cervical cancer is extremely low among HIV-positive women in India.Objectives Given the limited usefulness of cytology-based screening programs, the current study retrospectively evaluated the comparative performance of visual inspection with 5% acetic acid (VIA), conventional cytology, and human papillomavirus (HPV) testing among HIV-positive women attending the cancer screening clinic at the tertiary cancer center.Materials and Methods Retrospective analysis of 291 HIV-positive women attending cervical cancer screening services in a tertiary cancer center in Mumbai was undertaken. All underwent simultaneous screening with VIA, Pap cytology, and HPV DNA testing, followed by diagnostic colposcopy and histopathology. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) to detect cervical intraepithelial neoplasia (CIN) 2/3 on histology were estimated.Results The screen positivity rate for cervical cancer screening by VIA, high-risk HPV DNA, and Pap cytology was 35.7, 34.4, and 6.2% respectively. At the CIN2+ disease threshold, the sensitivity, specificity, PPV, and NPV estimates were 80.00% (59.30–93.17), 68.42% (62.46–73.96), 19.23% (15.46–23.67), 97.33% (94.30–98.77) for VIA; 80.00% (68.78–97.45), 70.68% (64.81–76.08), 22.00% (18.22–26.32), 98.43% (95.58–99.45) for HPV DNA; and 64.00% (42.52–82.03), 98.12% (95.67–99.39), 76.19% (56.13–88.89), 96.67% (94.50–98.00) for cytology (HSIL cutoff).Conclusion The diagnostic performance of VIA and HPV DNA was comparable and better than cytology indicating that VIA as a cost-effective cervical cancer screening test can be incorporated within the services under sexually transmitted diseases /HIV testing and counseling centers within the country.
Keywords: Human Papilloma Virus; Human immunodeficiency virus; cervical cancer screening